Differences in abundance and functional intensity of characteristic microorganisms of tea plant rhizosphere soils contribute to the differentiation of tea quality in different rocky zones - Jia, Xiaoli; Chen, Yiling; Wang, Yuhua; Lin, Shaoxiong; Li, Mingzhe; Wang, Tingting; Cheng, Pengyuan; Zhu, Bitong; Zhang, Qi; Ye, Jianghua; Wang, Haibin (Frontiers in Microbiology, 2025)
The formation of Wuyi rock tea’s “rock flavor” exhibits distinct zonal characteristics, potentially closely related to differences in its rhizosphere microbial communities. This study systematically analyzed rhizosphere soil and leaf samples from tea plants in authentic rocky zone (ZY), semi-rock zone (BY), and continent zone (ZC) zones to uncover the microbiological mechanisms influencing tea quality. Results revealed significant gradient differences in tea quality indices (catechin, theanine, and caffeine content) following ZY > BY > ZC. Soil physicochemical analysis revealed that ZY exhibited the highest contents of available nitrogen and phosphorus, while ZC demonstrated superior organic matter content. Microbial community analysis indicated that ZY possessed the highest microbial functional diversity but the lowest network complexity, with community construction dominated by random processes. Through machine deep learning, the study identified Obscuribacteraceae and Psoroglaena as two key characteristic microbial genera, whose abundance showed significant positive correlations with tea quality indices. Functional prediction analysis further indicated that these two genera were significantly enriched in specialized pathways such as photosynthesis and lichenization. Moreover, the abundance of these characteristic microorganisms showed significant positive correlations with their corresponding functional intensities, soil physicochemical indices, and tea quality indices. This study elucidated the soil microbial ecological basis for the formation of Wuyi rock tea quality across different rock zones from the perspectives of microbial community construction mechanisms and functional property. It provides theoretical support for understanding tea plant–soil-microorganism interactions and precision management in tea plantations.